The outsiders - Hinton, S. E. (New York Dell, 1967)
The struggle of three brothers to stay together after their parent's death and their quest for identity among the conflicting values of their adolescent society.
Reprint. Originally published: New York : Viking, 1967.
Keywords: Family life -- Fiction; Gangs -- Fiction